(untitled) (Damascus University Journal of arts and humanities sciences, 2021)
This study aspires to a critical approach to the text of the novelist from component time of the narrative components, due to what caused this component of the budged in the traditional perspective toward sex novelist, in general, and the components of the narrative is not framed its features yet, through to the effect of the use of time in the construction script, And what he achieves from the features of modernity that the novel seeks in its continuous search through various experimental methods.. Therefore, the study attempted to reveal the narrative effect of the temporal component in its focal work within the narrative text, so the choice was made on the novel (Inana and the River) by the Syrian novelist HalimBarakat, and then the research proceeded in order to reveal the articulations of the timeline of the narrative, to use it as a function In the construction of the narrative architecture inside the internal structure of the novel.